Disturbance effects of boat-based tourism on waterbirds at the Ramsar-designated De Hoop Vlei, Western Cape, South Africa - De Blocq Van Scheltinga, Andrew (Percy FitzPatrick Institute of African Ornithology, 2017)
Recreation and ecotourism activities are growing in demand worldwide, especially in biodiversity hotspots. Protected area managers may seek to introduce novel activities in order to generate revenue. However, disturbance effects brought about through encounters between humans and wildlife can have negative consequences, which conflict with conservation goals. De Hoop Vlei is a large coastal lake within the De Hoop Nature Reserve. It is a Ramsar site as well as a key feature of a BirdLife Important Bird Area (IBA). Proposals for motorized boat tours and kayak tours on the vlei have been made, for which this study provides an impact assessment. Repeated counts were performed in order to characterize the waterbirds present during the high water level conditions required for boating. Birds were concentrated in areas with aquatic vegetation and shallow water, mainly along the vlei's western shoreline and southern and northern ends. Two routes were designed for boat tours that would minimize disturbance by avoiding these areas as well as breeding sites. Count data were also used to revise the Ramsar and IBA assessments, which underestimated the site's conservation value. Boat tours were monitored to estimate the number of birds disturbed, and to measure agitation distances (ADs) and flight initiation distances (FIDs) in response to the boat as well as a kayak. Post-disturbance recovery was investigated, as was the likelihood of habituation using a space-for-time substitution at a site with regular boat traffic. Boat tours did not typically disturb more than 10% of birds present at the vlei, and largely avoided disturbing species of conservation concern. Responses to the kayak were more severe than to the boat, which is most likely due to the similar speeds of the two boats are similar and the kayak is more easily perceived as a threat due to its shape and stealth, the presence of a paddler, and the consistent paddling motion. Post-disturbance recovery of species was slow and incomplete after an hour, meaning that there are likely costs for foraging opportunities and breeding if important areas are disturbed. Most species did allow a closer approach at the site with regular boating, but AD did not differ between them for most species. From these results it would be dangerous to assume that habituation will mitigate against disturbance impacts. Recommendations made included that kayak tours should not be permitted. Boat tours, with correct management, can be conducted in a manner that will not be too disruptive to birds. This study is the first to document such a large difference in responses of birds to two differing boat types, and is a rare example of disturbance of birds being studied in an African context.